Stereotactic core ablative radiation therapy for small hypoxic tumors: impact of dosimetric approaches and consequent optimization strategy in the context of spatially fractionated radiation therapy - Xu, Zhengzheng; Balik, Salim; Woods, Kaley; Lim, Andrew; Ye, Jason C.; Chang, Eric L.; Lyons, Kristopher; Ma, Lijun; Shen, Zhilei; Lukas, Lauren; Zhang, Hualin (Frontiers in Oncology, 2025)
PurposeStereotactic core ablative radiation therapy (SCART) delivers a single ablative dose core to the central hypoxic part while keeping low doses to the periphery of the tumor. This study evaluated the dosimetric impacts of various SCART planning approaches for small targets in the context of spatially fractionated radiation therapy (SFRT).Methods and materialsUsing an anthropomorphic phantom, SCART plans were generated for cases with one spherical target, two spherical targets, one spherical target and one irregularly shaped target, and four spherical targets. All the spherical targets were 3 cm in diameter. One-third of the central gross target volume (GTV) was contoured as GTV_central to represent the hypoxic tumor volume, while the rest was contoured as GTV_peripheral for low-dose (3-Gy) coverage. Within each GTV, a small sphere with a diameter ranging from 0.5 to 1.5 cm was contoured at the center to represent the volume of a single high-dose core (V_SHDC). For the irregularly shaped target, both spherical (V_SHDC) and conformal (V_cSHDC) high-dose cores were used for comparisons. A single fraction of 15 Gy was prescribed to V_SHDC in all plans. Single- and dual-isocenter techniques were used for the case of two targets. Dosimetric parameters, which were usually used to describe SFRT plans, were compared for all SCART plans. The pros and cons of all planning approaches were elaborated.ResultsThe mean dose to V_SHDC was 17.0 ± 0.7 Gy. For multiple-target SCART plans, the peripheral GTV receiving less than 3 Gy (VGTVp<3Gy) ranged from 35.1% to 63.6%. No significant difference in dosimetric parameters was found between plans using a single isocenter and dual isocenters. For the irregularly shaped target, V_cSHDC improved the equivalent uniform dose (EUD) while the low-dose (3-Gy) coverage (VGTVp<3Gy) decreased. The average D10/D90 of all the plans was 8.0 ± 1.7. SCART used 1-cm-diameter V_SHDC (volume ratio of V_SHDC/GTV was within 2%–5%), demonstrating better dosimetric balance between high-dose coverage for GTV_central and low-dose coverage for GTV_peripheral.ConclusionSCART for small targets is feasible; the plans demonstrated a comparable dosimetric quality as seen in the traditional SFRT plans for bulky tumors.